Rare earth oxide modified Cf / ZrC-SiC composite material and preparation method thereof
Through high-frequency vibration-assisted grouting and polycarbosilane impregnation processes, the rare earth oxides are evenly dispersed into the Cf/ZrC-SiC composite material, which solves the problem of oxide film cracking in high-temperature environments, and improves the anti-oxidation and ablation performance and Mechanical performance meets the long-term reusable needs of hypersonic vehicles.
Patent Information
- Application Number
- CN202411308930.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-19
AI Technical Summary
Cf/ZrC-SiC composites are prone to ZrC oxidation and oxide film cracking in high-temperature aerobic environments, making it difficult for materials to be reusable for a long time. The modification effect of existing rare earth oxide coatings is limited.
Using high-frequency vibration-assisted grouting process and polycarbonsilane pioneer impregnation and cracking process, rare earth oxides are evenly dispersed into the Cf/ZrC-SiC composite material, and the residual stress between components is eliminated through post-high temperature heat treatment to improve material performance .
It significantly improves the anti-oxidation ablation and mechanical properties of the material, extends the service life of the material, and ensures the long-term reusable needs of hypersonic vehicles.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The present invention relates to a rare earth oxide modified C f The invention relates to a ZrC-SiC composite material and a preparation method thereof, belonging to the field of preparation of ultra-high temperature ceramic-based composite materials. f / Preparation method of modified ZrC-SiC composite material. Background Art
[0002] Due to the aerodynamic heating caused by the high Mach speed during the flight of hypersonic aircraft, the thermal protection materials need to face the harsh service environment of ultra-high temperature above 2000℃, high heat flux and chemical erosion of a large amount of gaseous oxides. Therefore, the thermal protection materials need to have the characteristics of high temperature resistance, excellent mechanical properties and anti-oxidation and ablation properties. f / ZrC-SiC composite materials have low density, low expansion coefficient, high specific strength, high temperature resistance, good anti-oxidation ablation performance and thermal shock resistance, making it the preferred material in the current thermal protection field, and have great application potential in the field of hypersonic aircraft thermal protection.
[0003] However, C f / In a high-temperature oxygen environment, ZrC in ZrC-SiC composites oxidizes to form ZrO2, accompanied by volume expansion, which easily leads to cracking of the oxide film and formation of microcracks. It is very easy to be peeled off under long-term high-speed gas scouring, which seriously limits the long-term and reusable use requirements of hypersonic aircraft. Studies have shown that by introducing a certain amount of rare earth oxides, the martensitic phase transformation of ZrO2 can be inhibited, and the volume mutation of ZrO2 can be reduced or eliminated, thereby achieving the effect of stabilizing the high-temperature phase of ZrO2. At present, the modification of C with rare earth oxides is a hot topic. f / ZrC-SiC composite materials are mainly used to prepare anti-oxidation coatings, which have a certain effect on stabilizing the high-temperature phase of ZrO2 and inhibiting the volatilization of SiO2. However, the effect of rare earth oxide coatings is relatively limited. Once the coating cracks and falls off, C f / ZrC-SiC composite materials are difficult to reuse for a long time.
[0004] At present, rare earth oxides are used to prepare anti-oxidation coatings modified by C f The preparation process of ZrC-SiC composite materials has limited effect and is prone to cracking and falling off. Therefore, it is very necessary to provide a method for uniformly dispersing rare earth oxides as matrix components and introducing them into C f / ZrC-SiC composite materials, thereby achieving the purpose of inhibiting SiO2 volatilization and stabilizing the high-temperature phase of ZrO2, ultimately meeting the long-term and reusable needs of hypersonic vehicles. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a rare earth oxide modified C f / ZrC-SiC composite material and its preparation method, the method uses high-frequency vibration assisted grouting process to uniformly disperse and inject micro-nano ZrC and nano rare earth oxide slurry with precisely controllable content into the carbon fiber preform. Combined with the polycarbosilane precursor impregnation and cracking process, C containing rare earth oxide is prepared f / ZrC-SiC composite material, and the residual stress between the components of the material is eliminated through a post-high temperature heat treatment process, thereby improving the overall performance of the material and achieving the requirement of reusable material.
[0006] The present invention also aims to provide a rare earth oxide modified C prepared by the above process. f / ZrC-SiC composites.
[0007] The technical solution of the present invention comprises the following steps:
[0008] Step 1: Preparation of carbon fiber preform: According to the harsh and complex service environment that hypersonic aircraft thermal protection materials need to face in service, such as ultra-high temperature (>2000℃), repeated alternation of hot and cold, and violent scouring of high-speed gas, this patent uses T1000 carbon fiber to weave into a three-dimensional needle-punched preform, in which the volume density of the carbon fiber preform is 0.18g / cm 3 ~0.20g / cm 3 .
[0009] Step 2: High-temperature heat treatment of carbon fiber preform: After the carbon fiber preform is clamped with a dimensional graphite tooling, it is placed in a high-temperature furnace and then evacuated to below 100 Pa. The carbon fiber preform is subjected to high-temperature heat treatment at 2300°C to 2500°C in the high-temperature furnace for 2 hours, during which Ar is introduced as a protective gas, and the pressure is maintained at 3000Pa to 5000Pa.
[0010] Step 3, preparation of PyC interface: firstly, a PyC interface is deposited on the carbon fiber preform after high temperature heat treatment by chemical deposition method, wherein the thickness of the PyC interface is 300nm to 500nm.
[0011] Step 4: prepare a mixed slurry of ZrC and rare earth oxides: the rare earth oxides are Y2O3 and Yb2O3. ZrC powder and rare earth oxide powder are weighed and mixed, added to anhydrous ethanol, and then a dispersant and a binder are added. Then, the mixture is put into a ball mill for ball milling, and finally a uniformly dispersed mixed slurry of ZrC and rare earth oxides is obtained.
[0012] Step 5, high-frequency vibration assisted injection of mixed slurry: Use an injector to evenly and disperse the ZrC and rare earth oxide mixed slurry into the carbon fiber preform. When resistance appears during the injection process, immerse the carbon fiber preform in a beaker containing the mixed slurry, and then perform ultrasonic high-frequency vibration. After the high-frequency vibration is completed, continue to inject grouting. After repeated multiple times, when the mixed slurry overflows from the inside of the fiber preform, it means that the ultrasonic vibration assisted injection of the mixed slurry process is completed.
[0013] Step 6: Drying: Place the carbon fiber preform injected with the mixed slurry into an oven for drying at a temperature of 120°C to 150°C for 3h to 5h. f / ZrC-Y2O3-Yb2O3 ceramic body.
[0014] Step 7: Densification of SiC matrix: Polycarbosilane precursor impregnation cracking process is used to densify C f / ZrC-Y2O3-Yb2O3 ceramic body is densified by SiC matrix, and rare earth oxide modified C is obtained after repeated impregnation and cracking. f / ZrC-SiC composites.
[0015] Step 8: Post-high temperature heat treatment: Due to the differences in thermal expansion coefficients of carbon fiber, PyC interface, ZrC, SiC and rare earth oxides, internal stress is easily generated inside the material during the preparation process. In order to release the residual stress between the components, it is necessary to modify the rare earth oxides. f The ZrC-SiC composites were post-heat treated in a nitrogen atmosphere.
[0016] Step 9: Preparation of SiC surface coating: Rare earth oxide modified C by chemical vapor deposition f SiC coating was prepared by deposition on the surface of ZrC-SiC composite material to seal the surface pores, and finally a C / ZrC-SiC composite material with dense surface and uniform rare earth oxide dispersion was obtained. f / ZrC-SiC composites.
[0017] Preferably, in step 3, the PyC interface preparation method is: placing the carbon fiber preform in step 2 in a chemical deposition furnace, using natural gas as a carbon source and nitrogen as a diluent gas to perform PyC interface deposition. The deposition process parameters are: deposition temperature of 980°C to 1050°C, natural gas flow rate of 15L / h to 20L / h, nitrogen flow rate of 15L / h to 20L / h, deposition time of 10h to 15h, and deposition pressure of 2000Pa to 2500Pa.
[0018] Preferably, in step 4, the method for preparing the mixed slurry of ZrC and rare earth oxide is as follows: ZrC powder with a particle size of 1.5 μm, Y2O3 with a particle size of 100 nm, and Yb2O3 with a particle size of 100 nm are mixed in a volume fraction ratio of 6:2:2 to 8:1:1, and the mixed powder of ZrC and rare earth oxide is added to anhydrous ethanol, wherein the volume fraction of the solid content in the mixed powder of ZrC and rare earth oxide is 30 vol.% to 40 vol.%, and then dispersant MW10000 polyethyleneimine and binder MW170000-250000 polyvinyl butyral are added. The mass ratio of polyethyleneimine, polyvinyl butyral to ZrC and rare earth oxide mixed powder is 0.01:0.01:1. Then, the mixture is placed in a ball mill and ball milled for 6 to 8 hours at a rotation speed of 200 r / min to 300 r / min to obtain a uniformly dispersed mixed slurry of ZrC and rare earth oxide.
[0019] Preferably, in step five, the high-frequency vibration-assisted injection of the mixed slurry method is: use a syringe with a needle aperture of 0.7mm to 1mm to spread the injection position of the preform from each plane along the center position to the surrounding equidistant, and inject the slurry into the preform evenly from deep to shallow. When resistance appears during the injection process, soak the preform in slurry with the same solid content, and then transfer it to a high-frequency ultrasonic vibration table for high-frequency vibration, with a vibration frequency of 500HZ to 800HZ and a vibration time of 20min to 30min. After the high-frequency vibration is completed, continue to inject the slurry into the preform with a syringe. After repeated multiple times, when the slurry overflows from the inside of the fiber preform, it means that the high-frequency vibration-assisted injection of the mixed slurry process is completed.
[0020] Preferably, in step seven, the SiC matrix densification method is: f The ZrC-Y2O3-Yb2O3 ceramic body is placed in a vacuum impregnation tank and evacuated to below 100 Pa. Then, a 30 wt% to 40 wt% polycarbosilane xylene solution is added to the impregnation tank to f / ZrC-Y2O3-Yb2O3 ceramic body is vacuum impregnated for 2h~3h. After vacuum impregnation is completed, it is placed in an oven for curing for 3h. The curing temperature is 250℃~300℃. After curing, it is placed in a cracking furnace for cracking to obtain a SiC ceramic matrix. The cracking temperature is 1100℃~1200℃, the heating rate is 5~10℃ / min, the insulation time is 1h~3h, and nitrogen is introduced as a protective gas. Repeat the above impregnation-curing-cracking process several times until C f / ZrC-Y2O3-Yb2O3 ceramic green body density reaches 2.5~3.0g / cm 3 Rare earth oxide modified C f / ZrC-SiC composites.
[0021] Preferably, in step eight, the post-high temperature heat treatment method is: modifying the rare earth oxide to C f The / ZrC-SiC composite material is placed in a high-temperature furnace with a heat treatment temperature of 1500°C to 1600°C. Nitrogen is introduced as a protective gas, the pressure is maintained at 3000Pa to 5000Pa, the heating rate is 50°C / h to 60°C / h, and the cooling rate is controlled at 60°C / h to 80°C / h during the cooling process.
[0022] Preferably, in step nine, the SiC surface coating preparation method is: modifying C f The / ZrC-SiC composite material is placed in a chemical deposition device, and trichloromethylsilane is used as a precursor, hydrogen is used as a carrier gas and a reaction gas, and argon is used as a diluent gas for SiC deposition. The deposition process parameters are: deposition temperature is 1100°C to 1300°C, trichloromethylsilane: hydrogen: argon flow ratio is 1:30:50, deposition time is 15h to 20h, and deposition pressure is 2000Pa to 3000Pa.
[0023] The rare earth oxide modified C f / ZrC-SiC composites.
[0024] The present invention is to solve the problem of preparing anti-oxidation coating modified C f The preparation process of ZrC-SiC composite materials has limited effect on stabilizing the high-temperature phase of ZrO2 and inhibiting the volatilization of SiO2, and is prone to cracking and falling off, which cannot meet the needs of long-term reusability of hypersonic aircraft. A unique high-frequency vibration-assisted grouting process, polycarbosilane precursor impregnation and cracking process and post-high-temperature heat treatment process are used to introduce rare earth oxides into C in a controllable and uniformly dispersed manner. f / ZrC-SiC composite materials, thereby achieving the purpose of improving anti-oxidation and ablation properties.
[0025] The rare earth oxide modified C prepared by the present invention f / ZrC-SiC composite materials have excellent mechanical properties. When the material is subjected to stress, the cracks will deflect between different interfaces and the ZrC-SiC matrix, greatly improving the toughness of the material, and the bending strength reaches 230MPa±25MPa.
[0026] The rare earth oxide modified C prepared by the present invention f / ZrC-SiC composites have excellent oxidation and ablation resistance, and the rare earth oxide modified C f / ZrC-SiC composite material was ablated for 100s, and the linear ablation rate was 0.24μm / s to 0.38μm / s. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The rare earth oxide modified C of the present invention f / ZrC-SiC composite material and its preparation flow chart;
[0028] FIG. 2 is a diagram of rare earth oxide modified C in Example 1 of the present invention. f Microstructure of / ZrC-SiC composite material. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described in conjunction with the embodiments and drawings. It is obvious that the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] Rare earth oxide modified C f Preparation method of ZrC-SiC composite material (such as Figure 1 ), including the following steps:
[0031] (1) Preparation of carbon fiber preform
[0032] The carbon fiber preform is woven into a three-dimensional needle-punched preform using T1000 carbon fiber, and the volume density of the carbon fiber preform is 0.18g / cm 3 ~0.20g / cm 3 .
[0033] (2) High temperature heat treatment of carbon fiber preform
[0034] After the carbon fiber preform is clamped with a dimensional graphite fixture, it is placed in a high-temperature furnace and then evacuated to below 100Pa. The carbon fiber preform is subjected to a high-temperature heat treatment at 2300℃~2500℃ in the high-temperature furnace for 2h. During the heat treatment, Ar is introduced as a protective gas and the pressure is maintained at 3000Pa~5000Pa. The graphite fixture is composed of two flat plates with uniform holes and bolt holes. The function of the fixture is to clamp the carbon fiber preform to prevent the carbon fiber preform from bending and deformation during the high-temperature heat treatment process.
[0035] (3) Preparation of PyC interface
[0036] Firstly, chemical deposition method is used to perform PyC interface deposition on the carbon fiber preform after high temperature heat treatment, wherein the thickness of the PyC interface is 300nm-500nm.
[0037] (1) Preparation of ZrC and rare earth oxide mixed slurry
[0038] The ZrC powder and the rare earth oxide powder are weighed and mixed, wherein the rare earth oxides are Y2O3 and Yb2O3. Then the obtained ZrC and rare earth oxide mixed powder is added into anhydrous ethanol, and then a dispersant and a binder are added, and then the mixture is put into a ball mill for ball milling, and finally a uniformly dispersed ZrC and rare earth oxide mixed slurry is obtained.
[0039] (5) High-frequency vibration assisted injection of mixed slurry
[0040] Use an injector to evenly and dispersedly inject the ZrC and rare earth oxide mixed slurry into the carbon fiber preform. When resistance appears during the injection process, immerse the carbon fiber preform in a beaker filled with the ZrC and rare earth oxide mixed slurry, and then perform ultrasonic high-frequency vibration. After the high-frequency vibration is completed, continue to inject grouting. After repeated multiple times, when the ZrC and rare earth oxide mixed slurry overflows from the inside of the carbon fiber preform, it means that the ultrasonic vibration-assisted injection of the ZrC and rare earth oxide mixed slurry is completed.
[0041] (6) Drying
[0042] The carbon fiber preform injected with ZrC and rare earth oxide mixed slurry is placed in an oven for drying at a temperature of 120°C to 150°C for 3h to 5h. After the treatment, C f / ZrC-Y2O3-Yb2O3 ceramic body.
[0043] (7) SiC matrix densification
[0044] The SiC matrix of Cf / ZrC-Y2O3-Yb2O3 ceramic green body was densified by polycarbosilane precursor impregnation and pyrolysis process, and rare earth oxide modified Cf / ZrC-SiC composite material was obtained after repeated impregnation and pyrolysis.
[0045] (8) Post-high temperature heat treatment
[0046] Due to the differences in thermal expansion coefficients among carbon fiber, PyC interface, ZrC, SiC and rare earth oxides, internal stress is easily generated inside the material during the preparation process. In order to release the residual stress between the components, it is necessary to modify the rare earth oxides. f The ZrC-SiC composites were post-heat treated in a nitrogen atmosphere.
[0047] (9) Preparation of SiC surface coating
[0048] Rare earth oxide modified C by chemical vapor deposition fSiC coating was prepared by deposition on the surface of ZrC-SiC composite material to seal the surface pores, and finally a C / ZrC-SiC composite material with dense surface and uniform rare earth oxide dispersion was obtained. f / ZrC-SiC composites.
[0049] The present invention will be further described below in conjunction with comparative examples and embodiments.
[0050] Comparative Example 1
[0051] This comparative example prepares a rare earth oxide modified C f / ZrC-SiC composite material, the preparation method comprises the following specific steps:
[0052] Step 1: Preparation of carbon fiber preform: The present invention uses T1000 carbon fiber to weave into a three-dimensional needle-punched preform, wherein the volume density of the carbon fiber preform is 0.18 g / cm 3 .
[0053] Step 2: High-temperature heat treatment of carbon fiber preform: After the carbon fiber preform is clamped with a dimensional graphite tooling, it is placed in a high-temperature furnace and then evacuated to 50 Pa. The carbon fiber preform is subjected to a high-temperature heat treatment at 2300°C in the high-temperature furnace for 2 hours, during which Ar is introduced as a protective gas and the pressure is maintained at 3000 Pa.
[0054] Step 3, preparation of PyC interface: Place the carbon fiber preform in a chemical deposition furnace to perform PyC interface deposition on the carbon fiber preform after high temperature heat treatment, using natural gas as the carbon source and nitrogen as the dilution gas for PyC interface deposition. The deposition process parameters are: deposition temperature of 980°C, natural gas flow rate of 10L / h, nitrogen flow rate of 10L / h, deposition time of 10h, deposition pressure of 2000Pa, and the thickness of the PyC interface after deposition is 210nm.
[0055] Step 4: Prepare ZrC slurry: Add ZrC powder with a particle size of 1.5 μm into anhydrous ethanol, wherein the volume fraction of the solid content of ZrC powder is 30 vol.%, and then add dispersant MW10000 polyethyleneimine and binder MW170000-250000 polyvinyl butyral. The mass ratio of polyethyleneimine, polyvinyl butyral to ZrC powder is 0.01:0.01:1. Then put it into a ball mill and mill it at a speed of 200 r / min for 6 hours to obtain a uniformly dispersed mixed slurry of ZrC and rare earth oxides.
[0056] Step 5: Inject ZrC slurry: Use a syringe with a 0.7mm diameter needle to inject the ZrC slurry into the carbon fiber preform from each plane along the center to the surrounding equidistant distance, and inject the ZrC slurry into the carbon fiber preform evenly from deep to shallow. When the ZrC slurry overflows from the inside of the fiber preform, it means that the ZrC slurry injection process is completed.
[0057] Step 6: Drying: Place the carbon fiber preform injected with ZrC slurry into an oven for drying at a temperature of 120°C for 3 hours. f / ZrC ceramic body.
[0058] Step 7: Prepare a mixed impregnation solution of polycarbosilane and rare earth oxides. Weigh polycarbosilane (PCS) and rare earth oxides (Y2O3 and Yb2O3) at a mass ratio of 1:0.2:0.2, and then add them into a xylene solvent for stirring, wherein the mass fraction of PCS, Y2O3 and Yb2O3 solid powders is 35wt%, the stirring time is 6h, and the stirrer speed is 350r / min.
[0059] Step 8: Densification of SiC-Y2O3-Yb2O3 matrix: f The ZrC ceramic body was placed in a vacuum impregnation tank and evacuated to 60 Pa. Then, a 35 wt% PCS-Y2O3-Yb2O3 xylene solution was added to the tank to impregnate the C f / ZrC ceramic body was vacuum impregnated for 2h. After vacuum impregnation, it was placed in an oven for curing for 3h. The curing temperature was 250℃. After curing, it was placed in a cracking furnace for cracking to obtain SiC-Y2O3-Yb2O3 matrix. The cracking temperature was 1100℃, the heating rate was 5℃ / min, the insulation time was 1h, and nitrogen was introduced as protective gas. The above impregnation-curing-cracking process was repeated 5 times to obtain rare earth oxide modified C f / ZrC-SiC composite material, density 2.24g / cm 3 .
[0060] Step 9: Post-high temperature heat treatment: Modify rare earth oxides into C f The / ZrC-SiC composite material was placed in a high-temperature furnace with a heat treatment temperature of 1500°C. Nitrogen was introduced as a protective gas, the pressure was maintained at 3000Pa, the heating rate was 50°C / h, and the cooling rate was controlled at 60°C / h during the cooling process.
[0061] Step 10: Preparation of SiC surface coating: Rare earth oxide modified C by chemical vapor deposition f / ZrC-SiC composite material surface deposition to prepare SiC coating for surface sealing, trichloromethylsilane as precursor, hydrogen as carrier gas and reaction gas, argon as dilution gas for SiC deposition. The deposition process parameters are: deposition temperature of 1100℃, trichloromethylsilane: hydrogen: argon flow ratio of 1:30:50, deposition time of 10h, and deposition pressure of 2000Pa.
[0062] The rare earth oxide modified C prepared in this comparative example f / ZrC-SiC composite material is 2.36g / cm 3 The room temperature flexural strength is 193.7MPa. The composite material was ablated at 2100℃ for 100s, and the linear ablation rate was 0.52μm / s.
[0063] Embodiment 1:
[0064] Step 1: Preparation of carbon fiber preform: The present invention uses T1000 carbon fiber to weave into a three-dimensional needle-punched preform, wherein the volume density of the carbon fiber preform is 0.18 g / cm 3 .
[0065] Step 2: High-temperature heat treatment of carbon fiber preform: After the carbon fiber preform is clamped with a dimensional graphite tooling, it is placed in a high-temperature furnace and then evacuated to 50 Pa. The carbon fiber preform is subjected to a high-temperature heat treatment at 2300°C in the high-temperature furnace for 2 hours, during which Ar is introduced as a protective gas and the pressure is maintained at 3000 Pa.
[0066] Step 3, preparation of PyC interface: Place the carbon fiber preform in a chemical deposition furnace to perform PyC interface deposition on the carbon fiber preform after high temperature heat treatment, using natural gas as the carbon source and nitrogen as the dilution gas for PyC interface deposition. The deposition process parameters are: deposition temperature of 980°C, natural gas flow rate of 15L / h, nitrogen flow rate of 15L / h, deposition time of 10h, deposition pressure of 2000Pa, and the thickness of the PyC interface after deposition is 300nm.
[0067] Step 4, prepare ZrC and rare earth oxide mixed slurry: 1.5μm particle size ZrC powder and 100nm particle size Y2O3 and 100nm particle size Yb2O3 are mixed in a volume fraction ratio of 6:2:2, and then ZrC and rare earth oxide mixed powders are added to anhydrous ethanol, wherein the volume fraction of solid content in ZrC and rare earth oxide mixed powders is 30vol.%, and then dispersant MW10000 polyethyleneimine and binder MW170000-250000 polyvinyl butyral are added. The mass ratio of polyethyleneimine, polyvinyl butyral to ZrC and rare earth oxide mixed powder is 0.01:0.01:1. Then put it into a ball mill and ball mill it at a speed of 200r / min for 6 hours to obtain a uniformly dispersed ZrC and rare earth oxide mixed slurry.
[0068] Step 5, high-frequency vibration assisted injection of mixed slurry: Use a syringe with a needle aperture of 0.7mm to inject the carbon fiber preform from each plane along the center position to the surrounding equidistant, and inject the ZrC and rare earth oxide mixed slurry evenly from deep to shallow into the carbon fiber preform. When resistance appears during the injection process, soak the carbon fiber preform in a mixed slurry of ZrC and rare earth oxide with the same solid content, and then transfer it to a high-frequency ultrasonic vibration table for high-frequency vibration, with a vibration frequency of 500HZ and a vibration time of 20min. After the high-frequency vibration is completed, continue to use a syringe to inject the ZrC and rare earth oxide mixed slurry into the preform. After repeating this process 3 times, when the ZrC and rare earth oxide mixed slurry overflows from the inside of the fiber preform, it means that the high-frequency vibration assisted injection of the ZrC and rare earth oxide mixed slurry process is completed.
[0069] Step 6: Drying: Place the carbon fiber preform injected with ZrC and rare earth oxide mixed slurry into an oven for drying at a temperature of 120°C for 3 hours. f / ZrC-Y2O3-Yb2O3 ceramic body.
[0070] Step 7: Densification of SiC matrix: f The ZrC-Y2O3-Yb2O3 ceramic body was placed in a vacuum impregnation tank and evacuated to 60Pa. Then, a 30wt% polycarbosilane xylene solution was added to the tank to precipitate the C f / ZrC-Y2O3-Yb2O3 ceramic body was vacuum impregnated for 2 hours. After vacuum impregnation, it was placed in an oven for curing for 3 hours. The curing temperature was 250°C. After curing, it was placed in a cracking furnace for cracking to obtain a SiC ceramic matrix. The cracking temperature was 1100°C, the heating rate was 5°C / min, the insulation time was 1h, and nitrogen was introduced as a protective gas. The above impregnation-curing-cracking process was repeated 8 times to obtain rare earth oxide modified C f / ZrC-SiC composite material, density 2.5g / cm 3 .
[0071] Step 8: Post-high temperature heat treatment: Modify rare earth oxides into C f The / ZrC-SiC composite material was placed in a high-temperature furnace with a heat treatment temperature of 1500°C. Nitrogen was introduced as a protective gas, the pressure was maintained at 3000Pa, the heating rate was 50°C / h, and the cooling rate was controlled at 60°C / h during the cooling process.
[0072] Step 9: Preparation of SiC surface coating: Rare earth oxide modified C by chemical vapor deposition f / ZrC-SiC composite material surface deposition to prepare SiC coating for surface sealing, trichloromethylsilane as precursor, hydrogen as carrier gas and reaction gas, argon as dilution gas for SiC deposition. The deposition process parameters are: deposition temperature of 1100℃, trichloromethylsilane: hydrogen: argon flow ratio of 1:30:50, deposition time of 15h, and deposition pressure of 2000Pa.
[0073] The rare earth oxide modified C prepared in this example f The density of the ZrC-SiC composite material is 2.71 g / cm 3 The room temperature flexural strength is 235.8MPa, which is 21.73% higher than that of the control. f / ZrC-SiC composite material has silvery white metallic luster. ZrC matrix and Y2O3-Yb2O3 rare earth oxides are evenly attached to the carbon fiber surface. The matrix density is high. f / ZrC-SiC composites have excellent oxidation and ablation resistance, and the rare earth oxide modified C f The / ZrC-SiC composite material was ablated for 100s, and the linear ablation rate was 0.38μm / s, which was reduced by 26.92% compared with the control example.
[0074] Embodiment 2:
[0075] Step 1: Preparation of carbon fiber preform: The present invention uses T1000 carbon fiber to weave into a three-dimensional needle-punched preform, wherein the volume density of the carbon fiber preform is 0.20 g / cm3 .
[0076] Step 2: High-temperature heat treatment of carbon fiber preform: After the carbon fiber preform is clamped with a dimensional graphite tooling, it is placed in a high-temperature furnace and then evacuated to 80 Pa. The carbon fiber preform is subjected to a high-temperature heat treatment at 2500°C in the high-temperature furnace for 2 hours, during which Ar is introduced as a protective gas and the pressure is maintained at 5000 Pa.
[0077] Step 3, preparation of PyC interface: Place the carbon fiber preform in a chemical deposition furnace to perform PyC interface deposition on the carbon fiber preform after high temperature heat treatment, using natural gas as the carbon source and nitrogen as the dilution gas for PyC interface deposition. The deposition process parameters are: deposition temperature of 1050°C, natural gas flow rate of 20L / h, nitrogen flow rate of 20L / h, deposition time of 10h, deposition pressure of 2500Pa, and the thickness of the PyC interface after deposition is 500nm.
[0078] Step 4, prepare ZrC and rare earth oxide mixed slurry: 1.5μm particle size ZrC powder and 100nm particle size Y2O3 and 100nm particle size Yb2O3 are mixed in a volume fraction ratio of 8:1:1, and then the ZrC and rare earth oxide mixed powder is added to anhydrous ethanol, wherein the volume fraction of the solid content in the ZrC and rare earth oxide mixed powder is 40vol.%, and then the dispersant MW10000 polyethyleneimine and the binder MW170000-250000 polyvinyl butyral are added. The mass ratio of polyethyleneimine, polyvinyl butyral to ZrC and rare earth oxide mixed powder is 0.01:0.01:1. Then put it into a ball mill and ball mill it at a speed of 300r / min for 8 hours to obtain a uniformly dispersed ZrC and rare earth oxide mixed slurry.
[0079] Step 5, high-frequency vibration assisted injection of ZrC and rare earth oxide mixed slurry: Use a syringe with a needle aperture of 0.7mm to inject the carbon fiber preform from each plane along the center position to the surrounding equidistant, and inject the ZrC and rare earth oxide mixed slurry into the carbon fiber preform evenly from deep to shallow. When resistance appears during the injection process, soak the carbon fiber preform in the ZrC and rare earth oxide mixed slurry with the same solid content, and then transfer it to a high-frequency ultrasonic vibration table for high-frequency vibration, with a vibration frequency of 800HZ and a vibration time of 30min. After the high-frequency vibration is completed, continue to use a syringe to inject the ZrC and rare earth oxide mixed slurry into the carbon fiber preform. After repeating 4 times, when the ZrC and rare earth oxide mixed slurry overflows from the inside of the carbon fiber preform, it means that the high-frequency vibration assisted injection of the ZrC and rare earth oxide mixed slurry process is completed.
[0080] Step 6: Drying: Place the carbon fiber preform injected with ZrC and rare earth oxide mixed slurry into an oven for drying at a temperature of 120°C for 3 hours. f / ZrC-Y2O3-Yb2O3 ceramic body.
[0081] Step 7: Densification of SiC matrix: f The ZrC-Y2O3-Yb2O3 ceramic body was placed in a vacuum impregnation tank and evacuated to 50Pa. Then, a 40wt% polycarbosilane xylene solution was added to the impregnation tank to f / ZrC-Y2O3-Yb2O3 ceramic body was vacuum impregnated for 2 hours. After vacuum impregnation, it was placed in an oven for curing for 3 hours. The curing temperature was 300°C. After curing, it was placed in a cracking furnace for cracking to obtain a SiC ceramic matrix. The cracking temperature was 1200°C, the heating rate was 10°C / min, the insulation time was 3 hours, and nitrogen was introduced as a protective gas. The above impregnation-curing-cracking process was repeated 10 times to obtain rare earth oxide modified C f / ZrC-SiC composite material, density 2.84g / cm 3 .
[0082] Step 8: Post-high temperature heat treatment: Modify rare earth oxides into C f The ZrC-SiC composite material was placed in a high-temperature furnace with a heat treatment temperature of 1600°C. Nitrogen was introduced as a protective gas, the pressure was maintained at 5000Pa, the heating rate was 60°C / h, and the cooling rate was controlled at 80°C / h during the cooling process.
[0083] Step 9: Preparation of SiC surface coating: Rare earth oxide modified C by chemical vapor deposition f / ZrC-SiC composite material surface deposition to prepare SiC coating for surface sealing, trichloromethylsilane as precursor, hydrogen as carrier gas and reaction gas, argon as dilution gas for SiC deposition. The deposition process parameters are: deposition temperature of 1100℃, trichloromethylsilane: hydrogen: argon flow ratio of 1:30:50, deposition time of 20h, deposition pressure of 3000Pa.
[0084] The rare earth oxide modified C prepared in this example f / ZrC-SiC composite material is 3.0g / cm 3 , the room temperature flexural strength is 253.7MPa. f / ZrC-SiC composite material was ablated for 100s, and the linear ablation rate was 0.24μm / s.
Claims
1. A rare earth oxide modified C f / ZrC-SiC composite material preparation method, characterized by: The following steps are involved: (1) Preparation of carbon fiber preform T1000 carbon fiber is woven into a three-dimensional needle-punched preform; (2) High temperature heat treatment of carbon fiber preform The carbon fiber preform is placed in a high-temperature furnace and then evacuated to below 100Pa; the carbon fiber preform is subjected to a high-temperature heat treatment at 2300°C to 2500°C in the high-temperature furnace for 2 hours, during which Ar is introduced as a protective gas and the pressure is maintained at 3000Pa to 5000Pa; (3) Preparation of PyC interface Firstly, chemical deposition is used to perform PyC interface deposition on the carbon fiber preform after high temperature heat treatment, wherein the deposition process parameters are as follows: deposition temperature is 980°C to 1050°C, natural gas flow rate is 15L / h to 20L / h, nitrogen flow rate is 15L / h to 20L / h, deposition time is 10h to 15h, and deposition pressure is 2000Pa to 2500Pa; (4) Preparation of ZrC and rare earth oxide mixed slurry The ZrC powder and the rare earth oxide powder are weighed and mixed, and then added into anhydrous ethanol, and then a dispersant and a binder are added, and then put into a ball mill for ball milling, and finally a uniformly dispersed ZrC and rare earth oxide mixed slurry is obtained; (5) High-frequency vibration assisted injection of mixed slurry Use an injector to uniformly and disperse the ZrC and rare earth oxide mixed slurry into the carbon fiber preform. When resistance appears during the injection process, the carbon fiber preform is immersed in a beaker filled with the ZrC and rare earth oxide mixed slurry, and then ultrasonic high-frequency vibration is performed. After the high-frequency vibration is completed, the grouting is continued. After repeated multiple times, when the ZrC and rare earth oxide mixed slurry overflows from the inside of the carbon fiber preform, it means that the ultrasonic vibration-assisted injection of the ZrC and rare earth oxide mixed slurry is completed; (6) Drying The carbon fiber preform injected with ZrC and rare earth oxide mixed slurry is placed in an oven for drying at a temperature of 120°C to 150°C for 3h to 5h. f / ZrC-Y2O3-Yb2O3 ceramic body; (7) SiC matrix densification C f The ZrC-Y2O3-Yb2O3 ceramic body is placed in a vacuum impregnation tank, and the vacuum is evacuated to below 100Pa. Then, a 30wt% to 40wt% polycarbosilane xylene solution is added to the impregnation tank to f / ZrC-Y2O3-Yb2O3 ceramic body is vacuum impregnated for 2h to 3h; after the vacuum impregnation is completed, it is placed in an oven for curing for 3h, the curing temperature is 250℃ to 300℃, and after the curing is completed, it is placed in a cracking furnace for cracking to obtain a SiC ceramic matrix, the cracking temperature is 1100℃ to 1200℃, the heating rate is 5 to 10℃ / min, the insulation time is 1h to 3h, and nitrogen is introduced as a protective gas; the above impregnation-curing-cracking process is repeated for many times until C f / ZrC-Y2O3-Yb2O3 ceramic green body density reaches 2.5~3.0g / cm 3 Rare earth oxide modified C f / ZrC-SiC composites; (8) Post-heat treatment Due to the differences in thermal expansion coefficients among carbon fiber, PyC interface, ZrC, SiC and rare earth oxides, internal stress is easily generated inside the material during the preparation process. In order to release the residual stress between the components, it is necessary to modify the rare earth oxides. f / ZrC-SiC composites were post-heat treated in nitrogen atmosphere; (9) Preparation of SiC surface coating Rare earth oxide modified C by chemical vapor deposition f The SiC coating was prepared by surface deposition on the ZrC-SiC composite material for surface sealing. Trichloromethylsilane was used as a precursor, hydrogen was used as a carrier gas and a reaction gas, and argon was used as a diluent gas for SiC deposition. Finally, a C / ZrC-SiC composite with a dense surface and uniform rare earth oxide dispersion was obtained. f / ZrC-SiC composite material; wherein the deposition process parameters are: deposition temperature of 1100°C to 1300°C, flow ratio of trichloromethylsilane: hydrogen: argon of 1:30:50, deposition time of 15h to 20h, and deposition pressure of 2000Pa to 3000Pa.
2. The rare earth oxide modified C according to claim 1 f / ZrC-SiC composite material preparation method, characterized by: In step (1), the volume density of the carbon fiber preform is 0.18 g / cm 3 ~0.20g / cm 3 .
3. The rare earth oxide modified C according to claim 1 f / ZrC-SiC composite material preparation method, characterized by: In step (3), the PyC interface deposition thickness is 300nm to 500nm.
4. The rare earth oxide modified C according to claim 1 f / ZrC-SiC composite material preparation method, characterized by: In step (4), when preparing a mixed slurry of ZrC and rare earth oxides, the ZrC powder has a particle size of 1.5 μm, the rare earth oxides are Y2O3 with a particle size of 100 nm and Yb2O3 with a particle size of 100 nm, the dispersant is polyethyleneimine with a MW of 10000 and the binder is polyvinyl butyral with a MW of 170000-250000, and ZrC, Y2O3 and Yb2O3 are mixed in a volume fraction ratio of 6:2:2 to 8:1:
1. The mixed powder of ZrC and rare earth oxides is added to anhydrous ethanol, wherein ZrC and rare earth oxides are mixed in anhydrous ethanol. The volume fraction of the solid content in the mixed powder of the chemical compound is 30vol.%~40vol.%, and then a dispersant MW10000 polyethyleneimine and a binder MW170000-250000 polyvinyl butyral are added, wherein the mass ratio of polyethyleneimine, polyvinyl butyral to ZrC and rare earth oxide mixed powder is 0.01:0.01:1, and then the mixed powder is put into a ball mill and ball milled at a speed of 200r / min~300r / min for 6~8 hours to obtain a uniformly dispersed ZrC and rare earth oxide mixed slurry.
5. The rare earth oxide modified C according to claim 1 f / ZrC-SiC composite material preparation method, characterized by: In step (5), the injector used is a syringe with a pore size of 0.7 mm to 1 mm, and the injection position of the carbon fiber preform is spread from the center position of each plane to the surrounding equidistant, and the injection depth is from deep to shallow to evenly inject the ZrC and rare earth oxide mixed slurry into the carbon fiber preform; When resistance appears during the injection process, the carbon fiber preform is immersed in a mixed slurry of ZrC and rare earth oxide with the same solid content, and then transferred to a high-frequency ultrasonic vibration table for high-frequency vibration. The vibration frequency is 500HZ~800HZ, and the vibration time is 20min~30min. After the high-frequency vibration is completed, the ZrC and rare earth oxide mixed slurry is continued to be injected into the carbon fiber preform with a syringe. After repeated multiple times, when the ZrC and rare earth oxide mixed slurry overflows from the inside of the carbon fiber preform, it means that the high-frequency vibration-assisted injection of the ZrC and rare earth oxide mixed slurry process is completed.
6. The rare earth oxide modified C according to claim 1 f / ZrC-SiC composite material preparation method, characterized by: In step (8), the post-high temperature heat treatment process parameters are 1500°C to 1600°C, nitrogen is introduced as a protective gas, the pressure is maintained at 3000Pa to 5000Pa, the heating rate is 50°C / h to 60°C / h, and the cooling rate is controlled at 60°C / h to 80°C / h during the cooling process.
7. The rare earth oxide modified C according to claim 1 f / ZrC-SiC composite material preparation method, characterized by: In the step (2), the carbon fiber preform is clamped with a graphite tool and then placed in a high-temperature furnace.
8. The method according to any one of claims 1 to 7 is used to prepare rare earth oxide modified C f / ZrC-SiC composites.
Citation Information
Patent Citations
Preparation method of Cf-ZrB2 / ZrC / SiC composite material
CN103332944A
Preparation method of three-dimensional carbon fiber toughened ultrahigh-temperature ceramic-based composite material with high breaking work
CN108558422A
Carbon fiber-reinforced (carbon-) silicon carbide base-ultra-high temperature ceramic base compound material and production method thereof
CN109970460A
Strong-ablation-resistant rare earth modified ultra-high-temperature ceramic-based composite material and preparation method thereof
CN113526972A
Cf / C-SiC composite material for engine piston and preparation method thereof
CN113698222A
Cited By
Fiber-reinforced ultrahigh-temperature ceramic-based composite material and preparation method thereof
CN119751103A
Composite material as well as preparation method and application thereof
CN120174335A
Preparation method of aviation carbon / carbon brake disc and aviation carbon / carbon brake disc
CN122647250A
